The Influence of Service Quality and Facilities on Student Satisfaction at Dr. Soetomo University with Brand Image as an Intervening Variable (Maneggio, 2025)
This study seeks to examine the impact of service quality and facilities on student happiness at Dr. Soetomo University, utilizing brand image as a mediating variable. The context of this research is based on the challenges faced by Dr. Soetomo University in maintaining and increasing the number of students, amidst tight competition between universitiesIn order to fulfil student expectations, the quality of services and facilities must be improved, as evidenced by the recent fall in student enrolment. This study tests the association between variables using a quantitative approach and path analysis tools. Data were obtained through questionnaires distributed to students of Dr. Soetomo University, which were then analyzed using various statistical tests to determine the validity, reliability, and significance of the relationship between variables. The results indicated that student satisfaction is significantly influenced by the quality of service and the availability of facilities. Furthermore, brand image was demonstrated to mediate the association between service quality and facilities with student satisfaction. A positive brand image can increase student satisfaction even though there are shortcomings in service quality or facilities. These findings indicate that in order to improve student satisfaction, Dr. Soetomo University needs to focus on improving brand image in addition to improving service quality and facilities. This research makes a significant contribution to university management in understanding the factors that influence student satisfaction. The implication is that Dr. Soetomo University is advised to improve its brand image through effective communication strategies and overall service improvements.